2019
DOI: 10.1128/jcm.01777-18
|View full text |Cite
|
Sign up to set email alerts
|

Virulence-Related Genes and Coenteropathogens Associated with Clinical Outcomes of Enteropathogenic Escherichia coli Infections in Children from the Brazilian Semiarid Region: a Case-Control Study of Diarrhea

Abstract: Enteropathogenic Escherichia coli (EPEC) is a major cause of diarrhea in children from developing countries and presents high genetic variability. We aimed to characterize the EPEC virulence-related gene (VRG) distribution and copathogens associated with diarrhea and nutrition-related outcomes in children from the lowincome Brazilian semiarid region. A cross-sectional case-control study of diarrhea was conducted in 1,191 children aged 2 to 36 months from the northeast region of Brazil. Stool samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Conflicting findings have also been reported concerning the association between MSD and the remaining DEC, aEPEC, EAEC, and STEC. The lack of a relationship that we observed in VIDA corroborates negative findings from recent studies that included Etiology, Risk Factors, and Interaction of Enteric Infections and Malnutrition and the Consequences for Child Health and Development project (MAL-ED) [ 10 ] and others [ 3 , 10 , 25 , 30 ]. Among the 7 sites and 3 age strata in GEMS [ 23 ], EAEC was only associated with endemic MSD in children aged 12–23 months from Bangladesh [ 31–33 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Conflicting findings have also been reported concerning the association between MSD and the remaining DEC, aEPEC, EAEC, and STEC. The lack of a relationship that we observed in VIDA corroborates negative findings from recent studies that included Etiology, Risk Factors, and Interaction of Enteric Infections and Malnutrition and the Consequences for Child Health and Development project (MAL-ED) [ 10 ] and others [ 3 , 10 , 25 , 30 ]. Among the 7 sites and 3 age strata in GEMS [ 23 ], EAEC was only associated with endemic MSD in children aged 12–23 months from Bangladesh [ 31–33 ].…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence to suggest that DEC induce intestinal inflammation that can lead to growth and nutritional faltering even in the absence of diarrheal disease [ 8 , 25 , 44–50 ], particularly during the first 2 years of life. In addition, both tEPEC and EAEC were associated with an increased risk of death in GEMS within 2–3 months after onset of the MSD episode [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional case-control study involving Brazilian children aged 2–36 months found a stronger link between tEPEC (typical EPEC) infections and clinical severity of diarrhea and undernutrition, compared with the cases of aEPEC (atypical EPEC) infections. 17 On the basis of the presence of the Escherichia coli adherence factor (EAF) plasmid encoding bundle-forming pili (BFP), EPEC can be subgrouped into tEPEC and aEPEC. 18 Typical EPEC is usually linked to incidences of gastroenteritis, even severe diarrhea among infants, whereas aEPEC is associated with a wide array of clinical manifestations, ranging from asymptomatic colonization to prolonged diarrhea, based on different settings.…”
Section: Introductionmentioning
confidence: 99%